Problem Solving Skills of Health Management Students - Hatice Ulusoy; Nurperihan Tosun; Jebagı Canberk Aydın (Association of Nurse Managers, 2014)
OBJECTIVE: The aim of this study determined to the problem solving skills of health management students' METHODS: In this descriptive study The Problem Solving Inventory, was used for data collection. Sample was consisted of all the students at the Department of Health Management (N=230). Data were collected between March,4-8, 2013. In the analysis Chi square, Mann-Whitney U, One-Way ANOVA Kruskal-Wallis were used. RESULTS: 195 students participated in to the study. Average scores of Problem Solving Inventory among the students were X=82,12+-18,27. It was found that 3rd grade students' (73,92+-16,77) and those who thought that they have leadership skills (X=79,83+-17,21) have had high level problem solving skills(p<0,05). There were no significant differences between problem solving skills and some variables such as age, gender, parent' education level, economical status. CONCLUSION: Average problem solving skills of the students were medium but 3rd and 4th grade students' were higher than the other groups. It is concluded that university education has significant contribution to problem solving skills of the students.